THE APPLICATION OF BIM TECHNOLOGY IN CONSTRUCTION PROJECT MANAGEMENT - Kumar, Harish; Singh, Surender (International Journal of Psychosocial Rehabilitation, 2021)
Building Information Modeling (BIM) technology plays a crucial role in engineering project management within the construction industry, providing effective solutions for traditional management challenges related to schedule, quality, and cost. By leveraging BIM, construction teams can create virtual models based on real-world conditions, allowing them to identify design deficiencies and manage schedules, materials, environment, and funds more precisely. BIM also enables construction units to conduct pre-construction simulations, improving construction quality while aiding management in quickly analyzing project data to enhance cost efficiency. The construction industry should therefore prioritize BIM technology to optimize project scheduling, quality, and cost management fully.